Pola Pembiayaan Pendidikan Pondok Pesantren Salafi - Aldi Pajar Ramdani; Muhamad Raimudin; Iwan Sopwandin (CV. Biha Cendekia, 2025)
This study aims to analyze the educational financing patterns at the Manba'ul Ulum Awitali Islamic Boarding School, a Salafi Islamic boarding school located in a rural area and does not receive government assistance. This study uses a descriptive qualitative approach, with data collection techniques including participatory observation, structured interviews, and documentation. The results show that this Islamic boarding school is able to survive and thrive through a community-based financing system. The main sources of funding come from monthly student fees, alumni donations, community donations, and creative income from Islamic arts activities such as hadroh and marawis groups. Financial management is carried out collectively and transparently, although it does not yet use a modern accounting system. Furthermore, the Islamic boarding school's success in managing its financing is supported by the active involvement of all elements of the boarding school, including student guardians, alumni, and the surrounding community. Islamic values such as trustworthiness, sincerity, and blessings are the main principles in financial management practices. This financing model demonstrates the strong role of social capital and spirituality in supporting the sustainability of education. These findings indicate that traditional Islamic boarding schools can develop an independent, equitable, and sustainable financial system by optimizing internal potential, community participation, and existing social networks.